Association between anesthetic type and perioperative outcomes in pediatric patients undergoing elective surgery: An observational study - Sugandhini Boda; Rajeshwari K (Asian Journal of Medical Sciences, 2024)
Background: Pediatric surgeries require careful anesthetic choice. The impact of general anesthesia (GA) versus regional anesthesia (RA) on post-operative outcomes remains underexplored. Aims and Objectives: The aims and objectives of the study are to assess the association between anesthetic type and perioperative outcomes, including post-operative pain, nausea incidence, and recovery room stay duration in pediatric patients undergoing elective surgery. Materials and Methods: This observational study involved 100 pediatric patients undergoing elective surgery. Participants were grouped based on the anesthetic received: GA or RA. Outcomes measured included post-operative pain (0–10 scale), post-operative nausea incidence, and recovery room stay length. Results: The mean post-operative pain score for GA patients was 4.5 (standard deviation [SD]: 1.5), with most reporting scores between 3.0 and 6.0. For RA patients, the mean pain score was 3.8 (SD: 1.2), with the majority reporting scores between 2.6 and 5.0. Patients under RA had marginally reduced post-operative pain scores than those under GA. Regarding nausea, 56% of GA patients reported post-operative nausea, while only 36% of RA patients did. The mean recovery room stay for GA patients was 120 min (SD: 30 min), with most staying between 90 and 150 min. RA patients had an average stay of 100 min (SD: 25 min), with the majority staying between 75 and 125 min. Conclusion: Pediatric patients administered RA demonstrated slightly lower post-operative pain, decreased incidence of nausea, and a shorter recovery room stay compared to those given GA. These findings suggest potential benefits of RA in pediatric elective surgeries, although further research is warranted.